Estimates of penetrance for recurrent pathogenic copy-number variations - Rosenfeld, Jill A.; Coe, Bradley P.; Eichler, Evan E.; Cuckle, Howard; Shaffer, Lisa G. (Genetics in medicine, 2013)
Although an increasing number of copy-number variations are being identified as susceptibility loci for a variety of pediatric diseases, the penetrance of these copy-number variations remains mostly unknown. This poses challenges for counseling, both for recurrence risks and prenatal diagnosis. We sought to provide empiric estimates for penetrance for some of these recurrent, disease-susceptibility loci. We conducted a Bayesian analysis, based on the copy-number variation frequencies in control populations (n = 22,246) and in our database of >48,000 postnatal microarray-based comparative genomic hybridization samples. The background risk for congenital anomalies/developmental delay/intellectual disability was assumed to be ~5%. Copy-number variations studied were 1q21.1 proximal duplications, 1q21.1 distal deletions and duplications, 15q11.2 deletions, 16p13.11 deletions, 16p12.1 deletions, 16p11.2 proximal and distal deletions and duplications, 17q12 deletions and duplications, and 22q11.21 duplications. Estimates for the risk of an abnormal phenotype ranged from 10.4% for 15q11.2 deletions to 62.4% for distal 16p11.2 deletions. This model can be used to provide more precise estimates for the chance of an abnormal phenotype for many copy-number variations encountered in the prenatal setting. By providing the penetrance, additional, critical information can be given to prospective parents in the genetic counseling session. Genet Med 2013:15(6):478–481